PENERAPAN INTERNET OF THINGS (IOT) PADA SISTEM KONTROL DAN MONITORING LAMPU GEDUNG MENGGUNAKAN NODEMCU BERBASIS TELEGRAM - Wahyu Hadikristanto1; Muhammad Suprayogi2 (Jurnal SIGMA, 2019)
The need for light is to be one of the main necessities of human life today. Technological advances are helpful in many respects aspects of life especially in terms of light. Thanks to technological advances, humans rely not only on sunlight as a means of lighting everyday life because of the discovery of lights as a substitute for illumination at night. By utilizing Internet Of Things technology Now the lights can be controlled and monitoring only through mobile devices or computers that have telegram applications installed. Utilizing the bot or robot features in the Telegram Messenger application, now controlling the lights and checking the lamp conditions can be replaced by the role of Relay Module 2 Chanel, NodeMCU V3, and the sensor LDR Module that is connected to the Internet. These three components are set in such a way that the source code can be connected with botTelegram tokens. Keywords: lights, Internet of Things (IoT), Relay Module 2 chanel, NodeMCU V3, sensor LDR module, bot Telegram.